MANAJEMEN LABA PADA PERIODASEBELUM DAN SESUDAH PENAWARAN SAHAM PERDANA DI BURSA EFEK JAKARTA: ANALISIS DENGAN MODEL DEANGELO - Elisa Indah; Erny Ekawati (Jurnal Riset Akuntansi dan Keuangan, 2006)
The previous research fotmd empirical evidence about existence of earnings monagement of suuraunding IPO (Initial Public Offerings). Previous reseqrch also found that operating performance at period after IPO less than before IPO. The purposes of this research is to reexamine earnings management surrounding IPO and association earnings manog"*"it surrotmding IPO with the operating performance in Indonesiancapital market.This study uses the companies data conducting IPO on 88 /irms that went at Jakarta Stock Exchange for the periods 1995-2002. Company do not the included in industrial group of property, real estate and building construction, and industrial group of finance. The method used toexamine eantings management are the method that develop by DeAngelo.Ihe result of this study by using t-test is fomd that firms manage theiremnings to increqse reported income before IPO and after IPO. It meansthat IPO issuers make income increasing discretionary accruals in thefmancial statement before IPO and in the financial statement afier IPO.In this study by using double regression examination also found thatoperoting performance after IPO less than before IPO. This conditionis consequence firms conduct earnings managetnent before IPO untilhappen underperformance after IPO.Keywords z IPO, earnings management, income increasing discretionaryaccruals, operating performance, DeAngelo model.